REFLECTION OF THE MEANINGS OF THE WORDS (HALAL AND HARAM) IN THE KURDISH LANGUAGE - SABRI ALI, DR..SHERZAD (Journal of Duhok University, 2019)
The words "Halal" and "Haram” are two words entered Kurdish culture through Islamic and Arab culture. These words are used in different contexts and have different meanings. This study, entitled (Reflection of the meanings of the words (Halal and Haram) in the Kurdish language) tries to study the concept of these two words in the Kurdish language with an attempt to explain and indicate semantics and pragmatics concept of these two words in the region of Bhdainan, according to descriptive analytical approach. The main objective of this research is to explain the use of the words "Halal" and "Haram” in the field of semantics and pragmatics. The research consists of two chapters. The first chapter is entitled "Halal and Haram, concept and culture", and it deals with definition of "Halal" and "Haram”, culture and the use of these words the dictionaries and literature, while the second chapter is devoted to clarifying the meanings of the word "Halal" and "Haram”